2021
DOI: 10.3390/jof7100821
|View full text |Cite
|
Sign up to set email alerts
|

ε-poly-L-lysine Affects the Vegetative Growth, Pathogenicity and Expression Regulation of Necrotrophic Pathogen Sclerotinia sclerotiorum and Botrytis cinerea

Abstract: Microbial secondary metabolites produced by Streptomyces are applied to control plant diseases. The metabolite, ε-poly-L-lysine (ε-PL), is a non-toxic food preservative, but the potential application of this compound as a microbial fungicide in agriculture is rarely reported. In this study, the effect and mode of action of ε-PL on two necrotrophic pathogenic fungi, Sclerotinia sclerotiorum and Botrytis cinerea, were investigated. The results showed that ε-PL effectively inhibited the mycelial growth of S. scle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 67 publications
2
2
0
Order By: Relevance
“…ε-PL has strong antibacterial, antiviral, and antifungal activities [ 24 , 25 ]; therefore, it has been gradually applied in the field of plant disease control as a natural anti-microbial product in agriculture in recent years. ε-PL has been reported to inhibit the growth of fungal pathogens as an antifungal activity agent, inhibiting the mycelial growth and spore germination of Sclerotinia scleroriorum , B. cinerea , and Alternaria alternate [ 13 , 26 , 27 ] which was consistent with our results showing effective inhibition of the mycelial growth of Botrytis cinerea and Alternaria alternata by ε-PL ( Table 1 ). It is worth noting that ε-PL at 200 µg/mL had an inhibitory rate toward mycelial growth of 83.9% against A. alternata [ 13 ].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…ε-PL has strong antibacterial, antiviral, and antifungal activities [ 24 , 25 ]; therefore, it has been gradually applied in the field of plant disease control as a natural anti-microbial product in agriculture in recent years. ε-PL has been reported to inhibit the growth of fungal pathogens as an antifungal activity agent, inhibiting the mycelial growth and spore germination of Sclerotinia scleroriorum , B. cinerea , and Alternaria alternate [ 13 , 26 , 27 ] which was consistent with our results showing effective inhibition of the mycelial growth of Botrytis cinerea and Alternaria alternata by ε-PL ( Table 1 ). It is worth noting that ε-PL at 200 µg/mL had an inhibitory rate toward mycelial growth of 83.9% against A. alternata [ 13 ].…”
Section: Discussionsupporting
confidence: 91%
“…Meanwhile, ε-PL at the same concentration or lower did inhibit the mycelial growth of Sclerotinia scleroriorum and B. cinerea. ε-PL at 1200 µg/mL reduced the lesion by 76.28% and also reduced the necrotic lesion area significantly at 600–1500 µg/mL [ 27 ]. Our results also demonstrated broad-spectrum effects against 12 pathogenic fungi.…”
Section: Discussionmentioning
confidence: 99%
“…Similar research has reported that RP is least sensitive to different organic acids (Barbero-López et al, 2020 ). Our results are also consistent with previous research that EPL treatment causes a dose–response effect on various fungi, such as necrotrophic pathogenic fungi, Sclerotinia sclerotiorum and Botrytis cinerea , and fruit pathogens, Penicillium expansum and Colletotrichum gloeosporioides (Zhou et al, 2021 ; Bai et al, 2022 ; Lv et al, 2022 ).…”
Section: Resultssupporting
confidence: 93%
“…44 ε-PL is a broad-spectrum antibacterial polypeptide and a natural food preservative; it participates in host resistance to tobacco mosaic virus infection by inducing host defense signals, 45 and inhibits hyphal growth of Sclerotinia sclerotiorum and Botrytis cinereal. 46 However, the biocontrol function of S. albus has been reported only rarely. 33 Therefore, we speculated that the biocontrol effect of S. albus could be mediated by ε-PL.…”
Section: Discussionmentioning
confidence: 99%